2017
DOI: 10.1038/s41598-017-00906-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of AMA-M2 in human saliva: Potentials in diagnosis and monitoring of primary biliary cholangitis

Abstract: Serum anti-mitochondrial antibody type 2 (AMA-M2) is considered as a pivotal biomarker for the diagnosis of primary biliary cholangitis (PBC). However, serological tests have many limitations, including inconvenience, invasiveness, and infection risks. Thus, a less invasive approach to detect AMA-M2 titer is desirable. We examined salivary AMA-M2 of potential PBC patients and found that AMA-M2 could be detected only in saliva of serum AMA-M2-positive PBC patients, but not in saliva of serum AMA-M2-negative PBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…A previous study reported that IL-6 and IFN-γ levels were significantly increased in the saliva of PBC patients. Moreover, the IL-6 and IFN-γ levels in the saliva of PBC patients are positively associated with those in the sera of those patients [ 41 ]. Similarly, elevated levels of salivary IL-1β, IL-6, and secretory IgA in cirrhosis patients have also been reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that IL-6 and IFN-γ levels were significantly increased in the saliva of PBC patients. Moreover, the IL-6 and IFN-γ levels in the saliva of PBC patients are positively associated with those in the sera of those patients [ 41 ]. Similarly, elevated levels of salivary IL-1β, IL-6, and secretory IgA in cirrhosis patients have also been reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSPs are considered as carriers of odorants in insect chemoreception 2. They are typically found in various insect tissues and perform divergent functions 42. Here, we cloned MsepCSP5 from M. separata which shares high sequence similarity with other CSPs and possesses four conserved cysteine connected by two disulfide bonds between neighbor residues showing the typical characteristics of CSPs 43.…”
Section: Discussionmentioning
confidence: 99%
“…The development not only of refined testing for AMA but also the addition of other PBC-defining autoantibodies to the repertoire has led to an increasing proportion of PBC patients displaying autoantibodies and likely also to earlier diagnosis. Today, even non-invasive testing for AMA seems feasible as a recently published approach to test AMA in saliva has demonstrated ( 81 ). It remains unclear whether these autoantibodies are pathogenetically relevant.…”
Section: Autoantibodies In Pbcmentioning
confidence: 99%